Between a Rock and a Hard Place : The Monetary Policy Dilemma in Latin America and the Caribbean - Vegh, Carlos A.; Morano, Luis; Friedheim, Diego; Rojas, Diego (Washington, DC: World Bank, 2017)
After a growth slowdown that lasted six years (including a contraction of 1.3 percent last year), the Latin American and Caribbean (LAC) region is finally expected to resume positive growth in 2017, with market analysts forecasting real GDP growth of 1.2 percent for 2017 and 2.3 percent for 2018. The recovery, particularly in South America, will be led by a strong rebound in Argentina, which is expected to grow by 2.8 percent in 2017 and 3.0 percent in 2018, and Brazil, which is expected to resume positive growth as well, expanding by 0.7 percent in 2017 and 2.3 in 2018, after contracting for two consecutive years. The usual external drivers of growth (particularly commodity prices, and growth in China and U.S.) are expected to remain relatively neutral, which points to the need for the region to reinforce its own sources of growth (e.g., structural reforms, investment in infrastructure, and further international trade both within and outside the region). Unfortunately, the region finds itself in a weak fiscal situation with 28 out of 32 countries with an overall fiscal deficit, which implies that a gradual but sustained fiscal consolidation will be needed in the years ahead. The report's main focus (Chapter 2) is on the monetary policy dilemma faced by countries in LAC. When a typical commodity-exporter country in LAC is hit by, say, a negative terms of trade shock, real GDP falls, the currency depreciates, and inflation increases. The Central Bank faces the dilemma of (i) increasing policy rates to defend the currency/fight inflation, but at the cost of aggravating the recession or (ii) reducing the policy rate, thus stimulating output, but encouraging further depreciation and inflation. Traditionally, LAC countries have chosen the first option and have thus pursued procyclical monetary policy (i.e., increasing policy rates in bad times). Recently, however, many countries have been able to switch and become countercyclical (i.e., reducing policy rates in bad times), which enables them to prop up the economy in recessionary times (which is particularly important when lack of fiscal space precludes countercyclical fiscal policy).